2015
DOI: 10.1111/jnc.13356
|View full text |Cite
|
Sign up to set email alerts
|

Prothymosin‐alpha preconditioning activates TLR4–TRIF signaling to induce protection of ischemic retina

Abstract: Prothymosin-alpha protects the brain and retina from ischemic damage. Although prothymosin-alpha contributes to toll-like receptor (TLR4)-mediated immnunopotentiation against viral infection, the beneficial effects of prothymosin-alpha-TLR4 signaling in protecting against ischemia remain to be elucidated. In this study, intravitreal administration of prothymosinalpha 48 h before induction of retinal ischemia prevented retinal cellular damage as evaluated by histology, and retinal functional deficits as evaluat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
20
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 82 publications
(241 reference statements)
5
20
0
Order By: Relevance
“…Fluorescence immunostaining revealed that Iba-1-positive microglia were distributed in the retinal GCL and IPL of control mice (Fig. 6A), which is consistent with previous reports (Lin et al, 2012;Halder et al, 2013c;Halder et al, 2015). Retinal ischemia caused microglial activation in terms of morphological change, migration, increased population and Iba-1 intensity throughout different retinal layers seven days after the ischemic stress in vehicle-treated mice, compared with the retina of untreated mice (Fig.…”
Section: P 6 Q Peptide Inhibits Retinal Ischemia-induced Activation Osupporting
confidence: 90%
See 1 more Smart Citation
“…Fluorescence immunostaining revealed that Iba-1-positive microglia were distributed in the retinal GCL and IPL of control mice (Fig. 6A), which is consistent with previous reports (Lin et al, 2012;Halder et al, 2013c;Halder et al, 2015). Retinal ischemia caused microglial activation in terms of morphological change, migration, increased population and Iba-1 intensity throughout different retinal layers seven days after the ischemic stress in vehicle-treated mice, compared with the retina of untreated mice (Fig.…”
Section: P 6 Q Peptide Inhibits Retinal Ischemia-induced Activation Osupporting
confidence: 90%
“…Immunohistochemical data revealed that the distribution of GFAP-positive astrocytes was mainly in the retinal GCL of untreated mice (Fig. 5D), consistent with previous studies (Lin et al, 2012;Halder et al, 2013c;Halder et al, 2015). Following retinal ischemia, GFAP-positive astrocytes were activated in terms of morphological change, increased number and GFAP intensity throughout the GCL to ONL seven days after the ischemic stress ( Fig.…”
Section: P 6 Q Peptide Inhibits Retinal Ischemia-induced Activation Osupporting
confidence: 89%
“…As for the mechanism underlying proTα's neuroprotective role, it has been shown that the polypeptide is released via a nonclassical manner under ischemic stress conditions and its extracellular release is facilitated by its interaction with a cargo molecule, namely S100A13 (Halder et al, 2012;Matsunaga & Ueda, 2010). Upon release, proTα activates the TLR4-TRIF-signaling pathway, inducing the expression of neuroprotective factors (Halder, Matsunaga, Ishii, & Ueda, 2015).…”
Section: Protα Exerts Neuroprotective Functionsmentioning
confidence: 99%
“…In 2010, Mosoian and colleagues confirmed that proTα ligates TLR4 and signals through both the TRIF-dependent and the MyD88 pathways for induction of IFN-β and proinflammatory cytokines, respectively (Mosoian et al, 2010). Most recently, proTα was shown to bind to the TLR4/MD-2 complex and activate the TRIF-IRF3-signaling pathway downstream TLR4 (Halder et al, 2015;Omotuyi et al, 2015).…”
Section: The Extracellular Role Of Protαmentioning
confidence: 99%
“…A leading theory is that the chronic neuro-inflammation generated by the activation of neuroglial cells (microglia, astrocytes, and Müller cells) which is involved in a number of complex signaling pathways [10, 11] in the retina after glaucoma [7, 8]. Recent studies have shown that activated neuroglial cells dramatically induced the activation of toll-like receptor 4-nuclear factor-kappa B (TLR4-NF-κB) pathways, which may play a vital role in promoting the release of pro-inflammatory cytokines, causing RGCs death in retina after optic nerve (ON) injury [11, 12]. There was evidence to show a reduced inflammatory responses and improved RGCs preservation following optic nerve crush (ONC) in TLR4-deficient mice, which indicated that the presence of TLR4-dependent pathway induced the RGCs death [13].…”
Section: Introductionmentioning
confidence: 99%